2020
DOI: 10.3390/ma13051031
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Low-temperature Annealing Process of Solution-processed TiO2 Electron Transport Layer for Flexible Perovskite Solar Cell

Abstract: Flexible perovskite solar cells (PSCs) have received increasing attention in wearable and portable devices over the past ten years. The low-temperature process of electron transport layer plays a key role in fabricating flexible PSCs. In this paper, we improve the performance of flexible PSCs by controlling the thermodynamic procedure in the low-temperature annealing process of solution-processed TiO2 layers and modulating the precursor concentration of (6,6)-phenyl c61 butyric acid methyl ester (PC61BM) depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…The ETL plays an important role in extracting electrons from the perovskite layer. It can prevent contact between the fluorine-doped SnO 2 (FTO) and perovskite layer to avoid the recombination of electrons and holes, and reduce energy loss at the interface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ETL plays an important role in extracting electrons from the perovskite layer. It can prevent contact between the fluorine-doped SnO 2 (FTO) and perovskite layer to avoid the recombination of electrons and holes, and reduce energy loss at the interface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that charge recombination is highly responsible for reducing the energy conversion efficiency of PSCs. Many researchers have focused on the ETL of PSCs [16,17,27]. Some investigators have tried to add a new layer into the ETL to form a bilayer, which has been demonstrated as an effective way to modify the interfacial behavior and photovoltaic performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The n-type metal oxide semiconductors, such as TiO 2 , [197] zinc oxide (ZnO), [198] tin dioxide (SnO 2 ), [199] tungsten trioxide (WO 3 ), [200] niobium pentoxide (Nb 2 O 5 ), [201] and aluminum oxide (Al 2 O 3 ), [202] have been used as ETLs in PSCs. Among these, TiO 2 has been most commonly used as the conventional ETL due to its low cost, simple fabrication procedures, environmental friendliness, high optical transparency, and matched energy levels with those of most perovskite materials.…”
Section: Electron Transport Layermentioning
confidence: 99%
“…Although organic materials have good solubility in the treatment process, their low electron mobility and high cost hinder the commercialization of PSCs. Inorganic materials, especially metal oxides [6][7][8][9][10][11][12][13][14][15][16][17][18], are endowed with superior advantages of low cost, high stability, and excellent photoelectric property [12,19,20], are usually used as electron transport layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides such as TiO 2 [6][7][8][9], ZnO [14,15], and SnO 2 [10][11][12][13][14]21], have become the mainstream materials of ETLs. Giordano and co-workers have demonstrated that the electronic trap states could be reduced and electron transport could be enhanced by introducing Li-ions into TiO 2 ETLs [22].…”
Section: Introductionmentioning
confidence: 99%